Re-evaluating disability assessment in war veterans with posttraumatic stress disorder - Samardžić Radomir M.; Živić Bratislav; Krstić Dragan; Joković Danilo; Dolić Mirko; Stojanović Zvezdana; Eror Aleksandar; Đokić Milan; Milojević Slavoljub; Mandić-Gajić Gordana (Vojnosanitetski Pregled)
Background/Aim. Sametimes war veterans may resort to such strategies as preducing exaggerated symptoms and malingerating in order to obtain material compensation rights. The aim of this study was to assess the accuracy of the diagnosis of posttraumatic stress disorder (PTSD) on the basis of which war veterans were entitled to a financial compensation due to their disability. Methods. The diagnoses of 259 war veterans were re-evaluated. Veterans were previously diagnosed by a psychiatrist on local level, while regional state medical commission determined the degree of disability and the right to a financial compensation. A team of experts, consisting of psychiatrists with research experience in the field of traumatic stress and who were trained to use a structured interview for PTSD, conducted the evaluation of medical data from veterans’ military records. The diagnostic process was conducted using the standardized diagnostic interview (Clinician-Administered PTSD Scale – CAPS), after which the diagnosis was reaffirmed or reviewed. This influenced disability status and consequential financial compensation. Results. There was a remarkable difference between the first diagnostic assessment of PTSD, conducted by the psychiatrists on local level, and the second evaluation conducted by the team of experts. In more than half of 259 veterans (52.1%) diagnosed with PTSD in the first assessment the diagnosis was not confirmed. The diagnosis was confirmed in 31.7% of veterans. Those veterans who were diagnosed with lifetime PTSD (7.3%) should also be treated as accuratelly diagnosed. This means that a total of 39% of the diagnoses were accurate. The rest (8.9%) were diagnosed with other diagnoses, but not PTSD, as was the case in the initial assessment. Conclusion. The possibility for war veterans to obtain the right to disability and financial compensation due to a diagnosis of PTSD might interfere with the proper diagnostic assessment and thus the treatment outcome. During the procedures for the obtention of these rights, exaggeration or simulation of symptoms are common. The quality of the diagnostic assessment of PTSD can be improved by applying evidence based standardized procedures.